La Celac más allá del regionalismo poshegemónico - Eduardo Crivelli; Giuseppe Lo-Brutto (Revista Iberoamericana de Estudios de Desarrollo)
In the beginning of the second decade of the 21st century, the Community of Latin American and Caribbean States (CELAC) seems to be the most finished expression of what was described as a «post-hegemonic regionalism», at a historical moment in which the Latin American States, without import their political profile, they agreed in questioning US hegemony and other powers in the region, in favor of a more just multipolar order. However, to the extent that regional political forces were reconfigured, the idea of this type of regionalism was questioned, especially for not reaching conclusive conceptualizations. Therefore, the objective of this article is to discuss the concept of post-hegemonic regionalism in Latin America from CELAC, which would have been the regional body that incubated the essential features of that conceptualization.